PENINGKATAN PERTUMBUHAN DAN HASIL CABAI BESAR (Capsicum annum L) MELALUI PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT DAN PUPUK HAYATI PADA TANAH PODSOLIK - Ramince Ramince; Zubaidah S (Fakultas Pertanian Universitas Palangka Raya, 2015)
This study aimed to determine the effect of compost oil palm empty fruit bunches and Biological Fertilizer on growth and yield great chili. The study was conducted in March-August 2014 at Jl. G. Obos 26, Kereng Bangkirai, Sebangau, Palangkaraya, This study used a completely randomized design (CRD) with two-factor factorial treatment. The first factor was the EFB compost consisting of 4 levels, namely: K0 = Without giving TKKS (0 g polybag-1); K1 = Giving TKKS (10.57 g polybag-1); K2 = Giving TKKS (21.14 g polybag-1); K3 = Giving TKKS (31.71 g polybag-1). The second factor was the provision of Biological Fertilizer (M) which consists of 4 levels, namely: M0 = Without giving Miza Plus (0 g polybag-1); M1 = Miza Plus (5.28 g polybag-1); M2 = Miza Plus (10.57 g polybag-1); M3 = Miza Plus (15.85 g polybag-1), so there are 16 combinations of treatment and repeated three times so that there are 48 units experiment. The results showed that there was an interaction on plant height and age 6 WAP and flower emergence occurred real influence number of productive branches, number of fruit and fresh fruit weight. The highest yield of fresh fruit heavy large pepper plants contained in a single treatment makes no compost TKKS K3 = (31.71 g polybag-1) and not significantly different with K2 = (21.14 g polybag-1), K1 = (10.57 g polybag-1); and the highest yield on a single factor giving Biological Fertilizer M2 (10.57 g polybag-1) and not significantly different from M3 = (15.85 g polybag-1)